Characterizations of groups with almost layer-finite periodic part - Senashov, V. I. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
Construction of the set of finite subgroups of the form L_g = a, a^g in Shunkov’s groups is studying. As a corollary of this result follows two characterizations of groups with an almost layer-finite periodic part.